Corporate Governance in Turkey: Issues and Practices of High-Performance Companies - Belverd E. Needles; Ahmet Turel; Evren Dilek Sengur; Asli Turel (Journal of Accounting and Management Information Systems (JAMIS), 2012)
This paper extends previous research, which investigated the relationship between performance and corporate governance practices. This study examines the concept of corporate governance in Turkey and compares compliance with good governance norms by high performance companies (HPCs) and comparable, but lower performing ordinary companies (ORD). It provides a background by explaining the problems of corporate governance and also briefly explains the regulatory framework in Turkey. The study is based on the published annual reports for the year 2010 of 60 ISE companies (30 HPCs and 30 ORDs). The research question examined is: Do companies that are demonstrably high performing companies in Turkey also exhibit good corporate governance compared to their paired peers? The key governance parameters, as per Turkish norms (Corporate Governance Principles of Turkey 2005), are selected on a 54-point scale. The study finds that Turkish companies generally, whether HPC (57.90 %) or ORD (50.68 %), score moderate measures of corporate governance. However, we find that HPCs in Turkey score higher on the norms of good corporate governance than comparable companies and the differences are statistically significant. Overall, these results strongly support the proposition that Turkish HPCs apply superior corporate governance practices and succeed to confirm conclusions of earlier research on HPCs in other economies. The paper concludes with limitations and outlining potential areas of corporate governance practices for further research.
Keywords: G34; M40; L10; 650; Corporate Governance; High Performance Companies; Turkey